Effects of Al substitution with Si and Sn on tribological performance of Ti3AlC2. Issue 5 (1st March 2021) - Cai, Leping; Huang, Zhenying; Hu, Wenqiang; Chen, Yexiao; Tan, Zeyi; Radovic, Miladin
Abstract: Since their discovery, the MAX phases have elicited engineering interest as potential choices for wear resistant parts. One such compound is Ti3 AlC2 with nano-layered structure, low density (4.25 g/cm 3 ), good oxidation resistant and self-lubrication properties. The purpose of this investigation was to evaluate the dominant effect of the A-site solid solution elements addition on dry sliding characteristics of Ti3 AlC2 against 0.45% C steel (S45C) disk, a material which is widely used in wear-critical applications such as impeller, gear and axles. Dry sliding tribological behaviors of hot-pressed Ti3 Al0.94 C2, Ti3 Al0.78 Sn0.22 C2 and Ti3 Al0.67 Si0.28 C2 solid solutions were conducted using a block-on-disk type tester at surface sliding speed range from 10 to 30 m/s and in the normal load range from 20 to 80 N. The results show that friction coefficient of Ti3 Al0.94 C2 is higher than that of Ti3 Al0.78 Sn0.22 C2, but lower than that of Ti3 Al0.67 Si0.28 C2 . However, the change in wear rate as a function of normal load for different sliding speed shows almost reversed trend. Difference in the phase composition of friction films were found to be responsible for observed change in tribological behaved after partial substitution of Al in Ti3 AlC2 with Sn and Si. This study shows that friction coefficient of Ti3 AlC2 can be adjusted from 0.2 to 0.38 by partially substituting Al with Si and/or Sn.